Halychyna. Journal of Regional Studies: Science, Culture, and Education. Twenty Years of Publishing Activity - Kuhutiak, Mykola; Raikivskyi, Ihor; Yehreshii, Oleh (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
This is a review of the twenty-year-long publishing activity of Halychyna. Journal of Regional Studies: Science, Culture and Education, one of the first Ukrainian journals for historians, philologists, art critics that appeared in the independent Ukraine. In Halychyna, there has been published the works by well-known scholars of Vasyl Stefanyk Precarpathian National University and many other higher educational establishments of Ukraine. The Journal can boast an array of sections – archaeology, history, ethnology, political science, historiography, source studies, documents and materials, culturology, art criticism, historical biography studies, and others. Most of the studies published in Halychyna focus on the issues of the modern and contemporary history of Ukraine, ethnology. A special attention is given to the issues of the Ukrainian national liberation movement in the 20th century, the Ukrainian national revival in the 19th–20th century, the activity of the political parties in Galicia in the late 19th–early 20th century, source studies and historiography in Ukraine, historical regional studies, the problems of modern state formation in Ukraine, and others